The Influence of Positive Self-Talk on Decision-Making of Young Futsal Athletes - Fathurochman, Rendy; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2025)
Futsal sports have very fast and dynamic game characteristics that require players to move quickly and dynamically on the field. During the match, the psychological changes of futsal athletes must change due to several factors such as stress, Concentration Stress, and mental pressure. Therefore, one of the mental skills that can be used when several of these factors occur is to use Positive Self-Talk skills. This study aims to determine the positive influence of self-talk on the decision- making of young futsal athletes. The method used is an experiment with a quantitative approach and one-group pretest-posttest design. The sample consisted of 12 futsal extracurricular students of SMAN 11 Bandung with a total sampling technique. The instrument used was the Decision Style Questionnaire (DSQ). The results showed there is a significant effects positive self-talk on decision-making of young futsal athletes. These findings suggest that positive self-talk is effective in improving decision-making in young futsal athletes. It is recommended that coaches incorporate mental self-talk training into training programs and that further research be conducted with a larger sample size and exploration of other types of self-talk.